The impact of macroeconomic news on quote adjustments, noise, and informational volatility - Nikolaus Hautsch; Dieter E. Hess; David Veredas (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We study the impact of the arrival of macroeconomic news on the informational and noise-driven components in high-frequency quote processes and their conditional variances. Bid and ask returns are decomposed into a common ('efficient return') factor and two market-side-specific components capturing market microstructure effects. The corresponding variance components reflect information-driven and noise-induced volatilities. We find that all volatility components reveal distinct dynamics and are positively influenced by news. The proportion of noise-induced variances is highest before announcements and significantly declines thereafter. Moreover, news-affected responses in all volatility components are influenced by order flow imbalances.
urn:nbn:de:hebis:30-75128
Keywords: C32; G14; E44; 330; Efficient Return; Macroeconomic Announcements; Microstructure Noise; Informational Volatility; Wirtschaftsinformation; Ankündigungseffekt; Börsenkurs; Bid-Ask Spread; Kapitalertrag; Informationseffizienz; Volatilität; Noise Trading; Mikrostrukturanalyse; Theorie; Schätzung; Zinstermingeschäft; Deutschland